From the World of the text toward the World of the reader (Ricoeur and Cortázar) (2010)
An interpretation of two authors, namely Paul Ricoeur and Julio Cortázar, is presented in this essay with respect to a couple of pieces of his respective works, namely, Tiempo y narración and Babas del Diablo. The purpose is to show how, in one hand, the